(untitled) - Lenka Mazalová; Elena Gurková; Lenka Machálková (University of Ostrava, 2023)
Aim: The study aimed to describe how undergraduate nursing students evaluated the clinical learning environment of their studies during the Covid-19 pandemic. Design: Longitudinal cohort study. Methods: The research sample of 49 full-time students who completed their first year clinical practice in the academic year of 2018/2019 was followed over three years of study. The Clinical Learning Environment, Supervision and Nurse Teacher evaluation scale (CLES+T) was used for data collection. Quantitative data were evaluated using descriptive and inductive statistics. Results: Overall, students evaluated the clinical environment throughout their studies as average. Interaction with a tutor received the lowest rating, while relationship with mentor and external factors of the clinical environment (nursing management and nursing care in the workplace) received the highest rating. Second-year students rated the practice environment most highly. Students were satisfied with individual supervision in the first two years. However, due to the Covid-19 pandemic, group supervision prevailed in the third year, resulting in reduced student satisfaction. Conclusion: Students' perception of the clinical learning environment changed during their studies. These changes were driven by the quality of certain academic and clinical factors. The Covid-19 pandemic represented a significant impingement on the course and organization of clinical practice.